Code Switching and Academic Performance Among Students - Fritzie L. Cempron; Wenie L. Nahial (Future Science / FSH-PH Publications, 2026)
This study aimed to determine the extent of code-switching utilization among the respondents in teaching English, Science, and Mathematics, as well as its association with the academic performance of the students. Thirty-nine (39) senior high school teachers agreed to serve as respondents of the study after meeting the requirements. Research protocols of DepEd-Camiguin were religiously observed in gathering the required data. Appropriate statistical tools were used to produce reliable results and sound insights. The descriptive statistics showed that females dominated in the teaching profile with a balanced distribution across age groups and experience levels. Analysis further revealed that the respondents had maintained a consistent, very high utilization of code-switching as a deliberate and strategic instructional tool. The students' academic performance was noted as being distributed between “Very Satisfactory” and “Outstanding” levels. The study found no significant relationship between code-switching and academic outcomes. This indicates that, as code-switching helped students to learn, this pedagogical approach does serve as a good predictor of the academic performance of the students. The study also found that respondents’ utilization of code-switching did vary significantly when grouped by sex, age, educational attainment, or years of teaching experience. It can be concluded then that the utilization of code-switching has become a routine among the respondents in the delivery of the lessons to the students.